How digital transformation curb greenwashing: Insights from fraud risk factor theory - Jiajun Xu; Rui Li (PLoS ONE, 2026)
This study investigates how digital transformation influences corporate greenwashing and promotes genuine sustainable development, drawing on the framework of fraud risk factors. Based on panel data from Chinese publicly listed companies between 2009 and 2022, a two-way fixed effects model is employed, with endogeneity addressed through difference-in-differences and instrumental variable techniques. The results show that digital transformation significantly curbs greenwashing by mitigating motivations, reducing opportunities, and enhancing exposure. The effect is stronger for growth- or mature-stage enterprises, non-myopic firms, and regions with low regulatory intensity and high environmental awareness. Furthermore, a double-threshold effect is identified, with the inhibitory role of digital transformation becoming more significant at intermediate and advanced stages. Importantly, digital transformation reduces greenwashing without compromising firms’ financial or sustainable performance. These results provide actionable insights for businesses and policymakers in curbing greenwashing and advancing sustainable development.